Are incomes a key determinant of the levels of household sight deposits during a financial market downturn? The case of the eurozone countries - Kochaniak, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The paper investigates the significance of households’ characteristics for the levels of their sight deposits in the eurozone countries – which, according to the European Banking Authority (EBA), are primarily dependent on household incomes. The analysis is based on household-level data and applies regression models. Its main finding is that the effect of annual gross incomes of households was statistically significant in most of the eurozone countries. However, a broader set of household characteristics revealed various mechanisms of the formation of sight deposits. The priority significance of incomes was confirmed only in four member states
Argumenta Oeconomica, 2019, Nr 2 (43), s. 5-37
Keywords: sight deposits; determinants; household characteristics